Phase-Controlled NiO Nanoparticles on Reduced Graphene Oxide as Electrocatalysts for Overall Water Splitting - Seung Geun Jo; Chung-Soo Kim; Sang Jun Kim; Jung Woo Lee (Nanomaterials, 2021)
Efficient water electrolysis is one of the key issues in realizing a clean and renewable energy society based on hydrogen fuel. However, several obstacles remain to be solved for electrochemical water splitting catalysts, which are the high cost of noble metals and the high overpotential of alternative catalysts. Herein, we suggest Ni-based alternative catalysts that have comparable performances with precious metal-based catalysts and could be applied to both cathode and anode by precise phase control of the pristine catalyst. A facile microwave-assisted procedure was used for NiO nanoparticles anchored on reduced graphene oxide (NiO NPs/rGO) with uniform size distribution in ~1.8 nm. Subsequently, the Ni-NiO dual phase of the NPs (A-NiO NPs/rGO) could be obtained via tailored partial reduction of the NiO NPs/rGO. Moreover, we demonstrate from systematic HADDF-EDS and XPS analyses that metallic Ni could be formed in a local area of the NiO NP after the reductive annealing procedure. Indeed, the synergistic catalytic performance of the Ni-NiO phase of the A-NiO NPs/rGO promoted hydrogen evolution reaction activity with an overpotential as 201 mV at 10 mA cm−2, whereas the NiO NPs/rGO showed 353 mV. Meanwhile, the NiO NPs/rGO exhibited the most excellent oxygen evolution reaction performance among all of the Ni-based catalysts, with an overpotential of 369 mV at 10 mA cm−2, indicating that they could be selectively utilized in the overall water splitting. Furthermore, both catalysts retained their activities over 12 h with constant voltage and 1000 cycles under cyclic redox reaction, proving their high durability. Finally, the full cell capability for the overall water electrolysis system was confirmed by observing the generation of hydrogen and oxygen on the surface of the cathode and anode.